Programming to Improve the Practical and Professional Competence of Future Teachers Based on A Differentiated Approach - Omarova Gavhar Sadikovna (Researchparks Publishing, 2026)
This article explores how the practical and professional legal competence of future teachers can be improved through a differentiated approach. It focuses on pragmatization—turning legal knowledge into usable skills—and works through the related ideas of diversification, integration, concept, and tendency. The author shows how grouping learners by level and need, linking law with other fields, and emphasising practical readiness all matter, arguing that legal competence is shifting from a fixed body of knowledge into a dynamic, person-centred skill.